Open-Pit Mine Geological Model Construction and Composite Rock Blasting Optimization Research - Yuqing Yang; Xiaohua Ding; Wei Zhou; Xiang Lu; Manda Ebelia; Wen An; Jinyu Li; Xiaonan Zhang (Shock and Vibration)
In this paper, the blasting parameters are designed based on the drilling data of the exploration geological stage, the geophysical and mechanical parameters of the mining area, and the geological age information, and the numerical simulation of the blasting of the layered rock steps is carried out to optimize the blasting parameters. Multiple sets of blasting tests were carried out on-site, and the large block rate, average block size satisfaction rate, large block satisfaction rate, cost satisfaction rate, shovel loading efficiency, and blasting effect satisfaction rate were set as the blasting effect evaluation indicators, which verified the feasibility of the optimized scheme.